2006
DOI: 10.1111/j.1467-8535.2006.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Building trust and shared knowledge in communities of e‐learning practice: collaborative leadership in the JISC eLISA and CAMEL lifelong learning projects

Abstract: Trust and collective learning are useful features that are enabled by effective collaborative leadership of e-learning projects across higher and further education (HE/FE) institutions promoting lifelong learning. These features contribute effectively to the development of design for learning in communities of e-learning practice. For this, reflexivity, good leadership and the capacity to engage in innovation is crucial to team performance. This paper outlines a serendipitously useful combination of innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Many HEIs have looked towards institutional e-learning strategies as ways of focusing efforts to adopt, diffuse and embed the use of learning technologies (see, for example, Lisewski, 2004). However, findings from the literature on innovation and organisational culture seem to support the notion that a less hierarchical model of project management is more supportive of innovation (Greenhalgh et al, 2004;Jameson et al, 2006;Jones and O'Shea, 2004). This implies that devising an institutional e-learning strategy and making adoption of learning technologies compulsory is unlikely to encourage longer-term sustaining and embedding.…”
Section: Educational and Organisational Changementioning
confidence: 67%
See 2 more Smart Citations
“…Many HEIs have looked towards institutional e-learning strategies as ways of focusing efforts to adopt, diffuse and embed the use of learning technologies (see, for example, Lisewski, 2004). However, findings from the literature on innovation and organisational culture seem to support the notion that a less hierarchical model of project management is more supportive of innovation (Greenhalgh et al, 2004;Jameson et al, 2006;Jones and O'Shea, 2004). This implies that devising an institutional e-learning strategy and making adoption of learning technologies compulsory is unlikely to encourage longer-term sustaining and embedding.…”
Section: Educational and Organisational Changementioning
confidence: 67%
“…This concept is particularly useful as it builds on the observation that learning technologists often have welldeveloped professional networks (Timmis, 2003), and suggests a way of theorising a less institutionally-bound and more informal, framework for collaboration. However, it is widely acknowledged that further work needs to be undertaken around the specific factors and organisational issues that contribute towards successful collaboration in the field of e-learning (Conole et al, 2006;Jameson et al, 2006;Lisewski, 2004;McPherson and Nunes, 2006;Mason and Lefrere, 2003).…”
Section: Rethinking Working Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior literature demonstrates that humility, humour and 'bottom up' practitioner empowerment can be stimulated through 'relational intelligence' intentionally fostered by the leaders of such communities. It has also been found that creative willingness to share leadership tasks and responsibilities in a distributed-coordinated team model enables successful teamwork (Jameson, Ferrell, Kelly, Walker and Ryan, 2006). To examine this, there is a need to consider distributed leadership as a response to situational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis is untenable, as shown by the data presented in this study; this striking difference in course design has direct impact on the same group of students' experience in different parts of the course. Numerous researchers have found that it is a challenging task to build up trust in online communities and contribute to positive online learning experience (e.g., Jameson et al 2006;Li 2011). A better understanding of the issue demands a careful consideration of the very nature of online communication and interaction and their implications for practice, which is independent of different actors' practice at any particular point of time.…”
Section: Introductionmentioning
confidence: 99%